Atmospheric ammonia measurements along the coastal lines of Southeastern China: Implications for inorganic nitrogen deposition to coastal waters. (March 2018) - Wu, Shui-Ping; Dai, Lu-Hong; Wei, Ya; Zhu, Heng; Zhang, Yin-Ju; Schwab, James J.; Yuan, Chung-Shin
Abstract: Ambient NH3 concentrations were determined using Ogawa passive samplers along the coastal lines of southeast China from June 2015 to May 2017. Additional monitoring of PM2.5 and precipitation around Xiamen Bay during the period from November 2015 to May 2017 were carried out to estimate atmospheric inorganic nitrogen (IN) deposition to the bay. Distinct seasonal variations of ambient NH3 were observed with summer averages 1.41–5.56 times higher than winter, which agreed well with the seasonal trend of air temperature. Nitrate concentrations (pNO3 - ) in PM2.5 were significantly higher than ammonium concentrations (pNH4 + ), and both species showed higher concentrations in winter and spring and lower values in summer and fall which were influenced mainly by the monsoon cycle, gas-to-particle transformation process and rain washout. Paired t-testing revealed that no significant differences of pNO3 - and pNH4 + between the urban and suburban sites around the Xiamen Bay. Unlike pNO3 - and pNH4 +, there were no clear seasonal trends for NH4 + and NO3 − concentrations in precipitation samples (wNH4 + and wNO3 - ). On average, the deposition of IN consisted of NH3 -N (27.4–28.2%) and pNO3 - -N (25.9–26.8%), followed by pNH4 + -N (17.0–17.7%), wNH4 + -N (14.5%), wNO3 - -N (13.3–13.8%) and NO2 -N (0.35–0.46%); and showed distinct seasonal trends with higher values in winter/spring and lower values in summer/fall. In 2016, the total IN deposition was determined to be 36.45 and 35.92 kg N ha −1 at the urban and suburban sites around the Xiamen Bay, respectively. The proportion of IN deposition to total IN loads (terrestrial + atmospheric), varied over the range of 7.1–13.3% depending on the data source of riverine influx. Our observations revealed that the total IN deposition could account for 9.6–25.1% (based on primary productivity over Taiwan Strait) and 1.7–5.3% (based on primary productivity in Guangdong coastal region) of new productivity in Xiamen Bay, respectively. As an important nutrient source, the atmospheric deposition of N could have significant impacts on coastal marine ecosystems. Graphical abstract: Highlights: Two-years NH3 observation along the southeast coast of China. Dry N deposition dominated (∼75%) total N deposition in Xiamen Bay. Reduced N forms accounted for 61% of total N deposition in Xiamen Bay. Atmospheric N deposition is a significant N nutrient input in Xiamen Bay.